Exigências de lisina digestível e energia metabolizável de codornas de corte (Coturnix cortunix sp) em crescimento, com base no conceito de proteína ideal - Ton, Ana Paula Silva (2007)
The aim of this experiment was to estimate the digestible lysine (DL) and metabolizable energy (ME) requirements for meat quails (Coturnix coturnix sp) on growing phase fed with diets formulated according to the ideal protein (IP) concept. A total of 1700 quails were used (4 until 35 days of age) of both sexes. The experimental design was a completely randomized in a factorial schedule of 4 x 4 (DL ? 0.92, 1.12, 1.32 and 1.52% x ME = 2,800; 2,900; 3,000 and 3,100 kcal/kg) with 16 treatments and 3 replications of 35 quails each one. The digestible aminoacids methionine+cystine, treonine and triptophan were supplied based, to the IP concept, on the DL levels. The results showed interaction (P<0,05) between DL and ME levels on period of 4 and 35 days of age for meat quails performance on growing phase. The estimative for better body weight (79.08g), body weight gain (65.02g) and accumulated biomass (463.26%) of quails were obtained with diets containing 1.44, 1.43 and 1.39% of DL during the period between 4 and 14 days, respectively. Feed consumption (FC) decreased linearly decrease (P<0.05) while feed:gain ration increased linearly (P<0.05) with the increase in the DL levels on diets during the period between 4 and 14 days. The better estimative for feed:gain ratio (2.78 g/g) for quails on period between 22 and 28 days of age was obtained with diet containing 1.26% of DL. Body weight, chess weight, carcass weight and yield, legs and back were not affected (P<0.05) by DL or ME of diet. Chest yield increased linearly with the increase in the LD levels while abdominal fat yield and weight increased linearly with the increase in the EM levels. The level of water on carcass had a linear decrease (P<0.05) with the increase on DL level while carcass fat level had a linear increase (P<0.05) with the increase on DL and ME levels. It was conclude that DL and ME requirements for maximum body weigh gain for meat quails (Coturnix coturnix sp) on growing phase fed with diets formulated according to the concept of ideal protein (IP), during the inicial period (4-14 days of age) were of 1.43% of DL and 2,800 kcal ME. For final period, 15 days until slaughter the better feed:gain ratio was estimated with 1.26% of LD.